2012
DOI: 10.7314/apjcp.2012.13.12.6159
|View full text |Cite
|
Sign up to set email alerts
|

Breast Self-examination Practices and the Effect of a Planned Training Program in Western Turkey

Abstract: This cross-sectional and descriptive study was aimed to evaluate women breast self-examination (BSE) practice and effects of a planned educational programme for breast cancer and BSE. The samples of the study consisted 266 women. The study data were collected by a questionnaire in six months periods as two times in a month in which the periods were defined and announced to all women. After that all the women were informed about BSE. The statue of performing BSE of women (n=146) was evaluated. They were intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
1
3
0
3
Order By: Relevance
“…Unlike Nigeria, where the most common sources of breast cancer information among market women were the elders, neighbours and friends [46], this study found that the radio and television were the most common sources of information on breast cancer and this confirmed what was reported from Iraq and Turkey [33] [47]- [49], that the media, both virtual and audio were prominent sources of breast cancer awareness. Thus, the high level of breast cancer awareness among study participants could be attributed to the proliferation of private television and radio stations in the country, most of which have programmes in the local languages and this attracts large listening audience.…”
Section: Discussionsupporting
confidence: 76%
“…Unlike Nigeria, where the most common sources of breast cancer information among market women were the elders, neighbours and friends [46], this study found that the radio and television were the most common sources of information on breast cancer and this confirmed what was reported from Iraq and Turkey [33] [47]- [49], that the media, both virtual and audio were prominent sources of breast cancer awareness. Thus, the high level of breast cancer awareness among study participants could be attributed to the proliferation of private television and radio stations in the country, most of which have programmes in the local languages and this attracts large listening audience.…”
Section: Discussionsupporting
confidence: 76%
“…In previous studies show that education has a positive effect over processes of knowing and acting associated with BSE (Thomas et al, 2002;Mc Cready et al, 2005;Beydag and Yurugen, 2010;Donmez et al, 2012;. In this study we think that the fact that the majority of the nursing students have performed BSE result from various factors such as they know how to do it, fear of having a cancerous mass, there are relatives who suffer breast cancer, they are conscious of the BSE benefits and aware of the effectiveness of BSE.…”
Section: Discussionmentioning
confidence: 97%
“…A study conducted in the Tekirdağ province (Gürdal et al, 2012) showed that 27.4% of women performed BSE regularly while 68.5% had performed at least one BSE. Donmez et al (Donmez et al, 2012) reported that 61.3% of subjects were unaware of breast evaluation and while 49.2% performed BSE, only 15.4% did so once each month. In the present study, 47.3% of participants in the control group and 33.3% of participants in the test group had performed a BSE within the past year.…”
Section: Discussionmentioning
confidence: 99%